Nocturnal relocation of adult and juvenile coral reef fishes in response to reef noise - Simpson, S.; Jeffs, A.; Montgomery, J.; McCauley, Robert; Meekan, M. (Springer Berlin Heidelberg, 2008)
Juvenile and adult reef fishes often undergo migration, ontogenic habitat shifts, and nocturnal foraging movements. The orientation cues used for these behaviours are largely unknown. In this study, the use of sound as an orientation cue guiding the nocturnal movements of adult and juvenile reef fishes at Lizard Island, Great Barrier Reef was examined. The first experiment compared the movements of fishes to small patch reefs where reef noise was broadcast, with those to silent reefs. No significant responses were found in the 79 adults that were collected, but the 166 juveniles collected showed an increased diversity each morning on the reefs with broadcast noise, and significantly greater numbers of juveniles from three taxa (Apogonidae, Gobiidae and Pinguipedidae) were collected from reefs with broadcast noise. The second experiment compared the movement of adult and juvenile fishes to reefs broadcasting high (>570 Hz), or low (<570 Hz) frequency reef noise, or to silent reefs. Of the 122 adults collected, the highest diversity was seen at the low frequency reefs; and adults from two families (Gobiidae and Blenniidae) preferred these reefs. A similar trend was observed in the 372 juveniles collected, with higher diversity at the reefs with low frequency noises. This preference was seen in the juvenile apogonids; however, juvenile gobiids were attracted to both high and low sound treatments equally, and juvenile stage Acanthuridae preferred the high frequency noises. This evidence that juvenile and adult reef fishes orientate with respect to the soundscape raises important issues for management, conservation and the protection of sound cues used in natural behaviour.